O jovem da escola pública e suas significações sobre seu futuro - Baciega, Solange Alves Silva (2012)
[Introduction] qualitative study that sought to analyze how the young, inserted at a public school in a city of Sao Paulo, means your future project, namely that meanings is not only about the project, as the process construction of the same. [METHODS] There were two different times to enable data collection: 1) proposed by the focus group discussion, 2) the dynamics of "Dialog Box". Complementary to these meetings became also an interview with the principal of the school unit. The analysis procedure was guided by the division of the significant speeches of the subjects into its categories. [RESULTS / DISCUSSION] The analysis led to the perception of the concerns of youth and uncertainties with regard to different aspects related to your own future project. The main points emerging were: the expectation of entering higher education, career choice, employment that provides a decent living; school as a socialization rich and fragile structure to prepare for professional life, lack of autonomy to meet the unique characteristics of each community training, support families, among others. [CONCLUSION] We concluded that young people in their needs and insecurities recognize the school as a facilitator in building your future project even aware of their fragilities